Ammonia and Nitrite Control Techniques in Vannamei Shrimp Cultivation Media at PT. Panen Berkat Sejahtera Bersama (PBSB) Sambelia, East Lombok - Setiawan, Rifky; Dwiyanti, Septiana (Aquaculture Department, University of Mataram, 2025)
Intensive cultivation of vannamei shrimp (Litopenaeus vannamei) requires good water quality management to support the growth, health, and survival of the shrimp. This research was conducted at PT. Panen Berkat Sejahtera Bersama (PBSB), East Lombok, for 25 days (April 9–May 3, 2025) with the aim of determining the control techniques for ammonia (NH₃) and nitrite (NO₂) in the cultivation media. The method used was descriptive with primary data collection through observation, active participation, interviews, and field documentation, as well as secondary data from company archives and related literature. The water quality management techniques applied included siphoning the pond bottom, waste disposal through a central drain system, and the use of Aquastar Pond probiotics. The water quality parameters observed included ammonia, nitrite, dissolved oxygen (DO), salinity, and pH. The results showed that ammonia levels were stable at 0.0000 mg/L and nitrite was in the range of 0.007–0.059 mg/L, remaining within safe limits for whiteleg shrimp. DO, salinity, and pH parameters were also within optimal ranges, supporting metabolism, osmoregulatory balance, and nitrifying microbial activity. The application of siphoning techniques, waste disposal, and probiotics has proven effective in maintaining stable water quality and creating optimal cultivation conditions for the growth and health of vannamei shrimp.